Analisis Faktor Ekonomi Sebagai Penyebab Perceraian pada Pengadilan Agama di Wilayah Hukum Pengadilan Tinggi Agama Surabaya pada Tahun 2023-2024 - Triana Apriyanita; Septiayu Restu Wulandari; Siti Auliya Baedarus (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
This study aims to analyze the influence of economic factors as a dominant cause of divorce within the jurisdiction of the Surabaya Religious High Court (PTA) from 2023–2024. The research findings indicate that economic factors play a significant role in disrupting domestic harmony, whether through the husband's inability to meet family needs, the increasing economic independence of women, or lifestyle pressures that exceed financial capabilities. This financial pressure often leads to stress, prolonged conflict, and unhealthy communication between spouses. Furthermore, shifting gender roles and weak family financial management also accelerate the breakdown of the marital relationship. This study concludes that economic stability is a primary pillar in maintaining domestic harmony. The results of this study are expected to serve as a basis for the Religious Courts and related institutions in formulating preventive and educational policies to reduce divorce rates attributed to economic factors